The Virginal Conception and Its Meanings - O'Collins, Gerald (New blackfriars, 2008)
In Jeffrey Archer's The Gospel According to Judas, Judas dismisses the virginal conception of Jesus as no more than another example of ‘Greek myths that tell of gods in heaven who produce offspring following a union with women of this earth’. To attribute such a view to a first-century Jew like Judas seems strange, since the earliest evidence shows Jewish critics of the Christian movement rejecting the virginal conception as a case of illegitimacy. In any case such Greek myths do not provide plausible sources for the two Gospel accounts of the virginal conception. Yet such merely historical debate is insufficient. One should press on to illustrate the religious significance and theological importance of the virginal conception within the whole story of Jesus: for instance, the role of this conception in revealing the Trinity at work for human salvation.